Stepwise artificial evolution of an Sw‐5b immune receptor extends its resistance spectrum against resistance‐breaking isolates of Tomato spotted wilt virus. Issue 11 (7th June 2021) - Huang, Haining; Huang, Shen; Li, Jia; Wang, Huiyuan; Zhao, Yaqian; Feng, Mingfeng; Dai, Jing; Wang, Tongkai; Zhu, Min; Tao, Xiaorong
Summary: Plants use intracellular nucleotide‐binding leucine‐rich repeat immune receptors (NLRs) to recognize pathogen‐encoded effectors and initiate immune responses. Tomato spotted wilt virus (TSWV), which has been found to infect >1000 plant species, is among the most destructive plant viruses worldwide. The Sw‐5b is the most effective and widely used resistance gene in tomato breeding to control TSWV. However, broad application of tomato cultivars carrying Sw‐5b has resulted in an emergence of resistance‐breaking (RB) TSWV. Therefore, new effective genes are urgently needed to prevent further RB TSWV outbreaks. In this study, we conducted artificial evolution to select Sw‐5b mutants that could extend the resistance spectrum against TSWV RB isolates. Unlike regular NLRs, Sw‐5b detects viral elicitor NSm using both the N‐terminal Solanaceae ‐specific domain (SD) and the C‐terminal LRR domain in a two‐step recognition process. Our attempts to select gain‐of‐function mutants by random mutagenesis involving either the SD or the LRR of Sw‐5b failed; therefore, we adopted a stepwise strategy, first introducing a NSm RB ‐responsive mutation at the R927 residue in the LRR, followed by random mutagenesis involving the Sw‐5b SD domain. Using this strategy, we obtained Sw‐5b L33P/K319E/R927A and Sw‐5b L33P/K319E/R927Q mutants, which are effective against TSWV RB carrying the NSm C118Y or NSm T120N mutation, and against other American‐type tospoviruses. Thus, we were able to extend the resistance spectrum of Sw‐5b; the selected Sw‐5b mutants will provide new gene resources to control RB TSWV.